Inovasi Pelayanan Aplikasi Ceria Terpadu Satu Pintu Kantor Wilayah Kementerian Agama Provinsi Jawa Timur - Rizki Amalia Oktaviana; Widyawati Widyawati; Nihayatus Sholichah; Ika Devy Pramudiana (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study explores the implementation and impact of the Ceria application, a digital integrated service platform developed by the Regional Office of the Ministry of Religious Affairs in East Java, Indonesia. The core objective of this digital innovation is to streamline bureaucratic processes, enhance the quality and efficiency of religious administrative services, and promote transparency and public participation. In the era of Industry 4.0, the transformation of public services through information and communication technology (ICT) has become imperative to meet increasingly complex societal demands for faster, more transparent, and accountable governance.Employing a qualitative research approach, the study collected data through interviews, observations, document analysis, and service usage statistics. The analysis revealed significant improvements in service delivery, notably a reduction in processing time from three to five days to merely one or two days, attributable to features such as real-time service status tracking and responsive complaint channels. These technological enhancements have contributed to strengthening public trust and satisfaction, reinforcing perceptions of professionalism and transparency within the ministry’s services. The application fosters a participatory culture by facilitating easier access for users, providing transparent information, and enabling active feedback, thus transforming bureaucratic practices into more adaptive, responsive, and user-centered processes.Despite these positive outcomes, the study identified critical challenges, primarily limited digital infrastructure in remote regions and disparities in digital literacy levels among users. Such barriers hinder equitable access to services and threaten the sustainability of digital initiatives. To address these issues, the study recommends ongoing infrastructural development, comprehensive digital literacy training, and community engagement to ensure that benefits are distributed inclusively across different societal groups.The findings underscore that such digital innovations are not merely technological upgrades but catalysts for cultural and institutional transformation. They promote ethical, moderate, and participative values that align with Indonesia’s national development agendas. Overall, the Ceria application exemplifies how strategic digital transformation can revolutionize public service delivery, fostering efficiency, transparency, inclusiveness, and trust. Future research may benefit from mixed-method approaches to examine broader impacts on user satisfaction, infrastructure readiness, and long-term sustainability. This case study offers valuable insights for policymakers and practitioners seeking to implement similar innovations to promote modern, accountable, and inclusive governance within religious and administrative services.